Membentuk Komunikasi Efektif Dalam Manajemen Konflik - Ida Ayu Gde Wulandari (Jayapangus Press, 2020)
Conflicts often occur in human life, both conflicts within themselves and with others. One source of conflict in human life is due to the inability of humans to communicate or not to communicate effectively. Effective communication between communicators and communicants will affect the message conveyed. If there is communication distortion, the message will not be conveyed properly. Effective communication will effectively solve the problem, or in other words effective communication between communicants and communicators has an influence in conflict management. In this paper we will explain about effective communication in conflict management.